THE ROLE OF PARENTAL GUIDANCE ON VOCABULARY ACHIEVEMENT IN AN INDONESIAN EFL ELEMENTARY EDUCATION SETTING - Christian Edison Bani; Sahiruddin Sahiruddin; Ika Nurhayani (Ma Chung Press, 2021)
Parental guidance can be seen as one of the determining factors to assist students in elevating their academic achievement. This study intends to discover the relationship between parental involvement and their children's second language (L2) vocabulary achievement, and the degree to which the levels of parents' educational background explain L2 vocabulary achievement. The data for this study were elicited from teachers' assessment of L2 vocabulary performance for 30 students and questionnaire responses involving 30 parents regarding parental involvements on their children’s learning. The study revealed that there was a significant correlation between parental involvement and students' vocabulary achievement in an Indonesian foreign language learning in an elementary school context. In addition, this study also demonstrated that parents' educational background explained the levels of support involvement which in turn influenced students' vocabulary achievement. The overall findings of this study also about the pivotal role of parental involvement and their educational background in enhancing their children’s achievement in terms of vocabulary learning are also discussed in terms of pedagogical implications.